Arguments for a Common Set of Principles for Collaborative Inquiry in Evaluation. (March 2013) - Cousins, J. Bradley; Whitmore, Elizabeth; Shulha, Lyn
In this article, we critique two recent theoretical developments about collaborative inquiry in evaluation—using logic models as a means to understand theory, and efforts to compartmentalize versions of collaborative inquiry into discrete genres—as a basis for considering future direction for the field. We argue that collaborative inquiry in evaluation is about relationships between trained evaluation specialists and nonevaluator stakeholders (i.e., members of the program community, intended program beneficiaries, or other persons with an interest in the program) and that practice should, in the first instance, be sensitive to stakeholder interests and context, and it should be principle-driven.